(untitled) (Jurnal Bina Praja, 2021)
Bandung is determined to be a focus location for national stunting interventions in 2020. Despite being one of the metropolitan cities in Indonesia, the prevalence of stunting in Bandung City is more than the WHO standard, so a strategy to reduce and handling of stunting is needed. Social and environmental aspects are essential to facilitate the policymaker. This study aims to analyze the stunting situation in Bandung City, then arrange Kelurahan based on the stunting risk index, to get an operative recommendation. The quantitative method analysis uses the concept of climate change adaptation which includes hazard and vulnerability indicators, while the qualitative method is formed by FGDs with key persons to identify problems and formulate impressive strategies. The results of the research showed that there are 15 Kelurahan that have the highest risk of stunting in Bandung City, to be intervention priority. These villages have relatively high poverty, poor access to sanitation, and low adaptive capacity. Recommendations from this study are increasing citizen knowledge of stunting through sustainable socialization and education, accelerating sensitive and specific stunting intervention programs, developing an integrated stunting data management system, and increasing participation also coordination among stakeholders.